Perkembangan Kemampuan Menjabarkan Ide dalam Menulis pada Siswa Kelas Atas SD Negeri 1 Segaran Kabupaten Malang - Sari, Nita Shinta; Suyono, Suyono; Sultoni , Achmad (Lembaga Teewan Journal Solutions, 2026)
This study aimed to examine upper-grade elementary students' ability to elaborate ideas in writing and determine its relationship with Indonesian language learning achievement at SD Negeri 1 Segaran, Malang Regency. A quantitative cross-sectional design was employed involving 31 students from Grades IV, V, and VI. Data were collected through writing tests, classroom observations, and students' report card scores. Writing ability was assessed using indicators of idea content, organization, coherence, and elaboration. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Spearman's rank correlation. The findings revealed that students' idea elaboration ability was generally at a moderate level, with idea content emerging as the strongest aspect, while coherence and elaboration remained relatively weak. Spearman's rank correlation demonstrated a positive and statistically significant relationship between students' idea elaboration ability and Indonesian language achievement across all grade levels. These findings suggest that stronger idea elaboration skills are associated with higher academic achievement in Indonesian language learning and highlight the importance of developing writing instruction that emphasizes idea generation, organization, and elaboration in elementary education.